An electrochemical nanobiosensor for plasma miRNA-155, based on graphene oxide and gold nanorod, for early detection of breast cancer - Azimzadeh, Mostafa; Rahaie, Mahdi; Nasirizadeh, Navid; Ashtari, Khadijeh; Naderi-Manesh, Hossein (Biosensors & bioelectronics, 2016)
Circulating miRNAs are emerging as novel reliable biomarkers for early detection of cancer diseases. Through combining the advantages of electrochemical methods and nanomaterials with the selectivity of the oligo-hybridization-based biosensors, a novel electrochemical nanobiosensor for plasma miR-155 detection have demonstrated here, based on thiolated probe-functionalized gold nanorods (GNRs) decorated on the graphene oxide (GO) sheet on the surface of the glassy carbon electrode (GCE). The reduction signals of a novel intercalating label Oracet Blue (OB), were measured by differential pulse voltammetry (DPV) method. The transmission electron microscope (TEM) imaging, UV–vis spectrophotometry, cyclic voltammetry (CV), field emission scanning electron microscope (FE-SEM) imaging and energy dispersive spectroscopy (EDS) were proved the right synthesis of the GNRs and correct assembly of the modified electrode. The electrochemical signal had a linear relationship with the concentration of the target miRNA ranging from 2.0fM to 8.0pM, and the detection limit was 0.6fM. Furthermore, the nanobiosensor showed high Specificity, and was able to discriminate sharply between complementary target miRNA, single-, three-base mismatch, and non-complementary miRNA. Alongside the outstanding sensitivity and selectivity, this nanobiosensor had great storage ability, reproducibility, and showed a decent response in the real sample analysis with plasma. In conclusion, the proposed electrochemical nanobiosensor could clinically be used in the early detection of the breast cancer, by direct detection of the plasma miR-155 in real clinical samples, without a need for sample preparation, RNA extraction and/or amplification. •An electrochemical nanobiosensor was developed for circulating miR-155 detection.•The graphene oxide and gold nanorods used to amplify the electrochemical signals.•A novel anthraquinone, Oracet Blue used as electroactive and intercalative label.•A wide linear range was obtained from 2fM to 8pM, and detection limit of 0.6fM.•The human plasma assay proved its potential for clinical breast cancer detection.